Career orientation and industry perceptions of Caribbean Hotel and Tourism Management students - Charles, Kwame R.
This paper presents the findings of a study of the career orientation and industry perceptions of undergraduate hotel management and tourism management students enrolled in the Hotel and Tourism Management Programme at The University of the West Indies (UWI). All students enrolled in the programme during the academic year 1989-90 were surveyed at the beginning and at the end of the year. The results of the study provide insights into these students' views about their career choices, working in the industry, perceived employment opportunities, and career path expectations. Major differences were found between students pursuing a hotel management degree as opposed to students pursuing a tourism management degree, among students from different territories in the region, and between the two surveys. The differences were found to be attributable primarily to students' industry internship experience. The findings of the study suggest that hotel and tourism management students may need more academic preparation and practical experience before entering the industry, and that the industry needs to be better prepared to receive and retain hotel and tourism management graduates
Keywords: Centre for Hotel and Tourism Management, UWI